Relations between tribal arbitration and Formal Judiciary - Alghushami, Hussein Ahmed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to gain insight on the Relations between tribal arbitration and formal judiciary by highlighting the legal effect of tribal judiciary procedures on rules issued by formal judiciary. To this end, the researcher applies a descriptive- analytical approach, through collecting data and jurisprudence on the relationship between tribal arbitration and formal judiciary to explore and use their opinions in understanding research dilemmas. In addition, the key data of the research will be collected through in- depth direct interviews with relevant stakeholders. The researcher reached a number of findings, the most important of which is that the relationship between the tribal arbitration and the systematic judiciary takes two main forms. The first is when the role of the tribal arbitration is limited to containing the conflict and putting an end to the reactions merely by arbitral awards and decisions. In this case, the function of the tribal arbitration is complementary to that of the regular judiciary. The function of the tribal arbitration is an alternative to the regular judiciary when the representatives of the tribal arbitration intervene in the dispute by issuing awards and rulings that deal with the outcome of the dispute. The study also demonstrates that the tribal arbitration plays a strategic role in resolving disputes. It further alleviates the great burden of cases dealt by the formal judiciary. Moreover, the study recommends the prerequisite for the organization of the customary judiciary in terms of precedents and rulings.